Comorbidities and survival in patients with chronic hypersensitivity pneumonitis - Wälscher, Julia (Respir Res, 2020)
INTRODUCTION: Chronic Hypersensitivity Pneumonitis (cHP) is a fibrotic interstitial lung disease (ILD) resulting from repeated exposure to an offending antigen. Prognostication in cHP remains challenging, and the relationship between comorbidities and survival has yet to be characterized. The aim of this study was to describe the relationship between comorbid conditions and survival in patients with cHP. METHODS: The prospective database from a tertiary referral centre for ILD was reviewed for patient-reported comorbidities, their frequency, and relationship with survival in cHP patients. Comorbidities were assessed by direct questioning of the patient at the baseline visit and by a standardized questionnaire for the diagnosis of interstitial lung diseases. During the follow-up examinations, patients were asked about newly diagnosed comorbidities. RESULTS: Two hundred eleven patients with cHP were identified (mean age 63 years, 53% male, mean FVC 73%), with mean follow-up of 32 months. The mean number of comorbidities was 3 (10% had 0, 59% 1–3 and 31% ≥4 comorbidities). Most frequent comorbidities groups were cardiovascular (65%) and respiratory (26%), most common comorbidities were hypertension (56%), gastro-esophageal reflux disease (GERD) (24%), diabetes (20%) and coronary heart disease (18%). In general, deceased patients had more comorbidities than survivors (p = 0.005), yet there was no association between the absolute number of comorbidities and survival. Pulmonary hypertension (30.8% versus 5.7%, p = 0.001;), diastolic dysfunction (26.9% versus 6.4%, p = 0.004) and cerebrovascular disease were more frequent in non-survivors (23.1% versus 7.6%, p = 0.026). Lung cancer was not observed, and neither GERD nor antacid drugs were associated with outcome (p = 0.357 and p = 0.961, respectively). CONCLUSIONS: Comorbidities are common in cHP are associated with survival. Further work should determine whether interventions for these specific comorbidities can positively affect survival.